Lipidoptera morphological structure as a basic of toxonomy in the area of lafarge cement indonesia plant in Lhoknga, Aceh Besar Distric, Indonesia - M. Ali Sarong; . Wardiah; M. D. Asiah; Samsul Kamal (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
.  The study of Lepidoptera that took place around the factory of Lafarge Cement Indonesia (LCI) was aimed to determine the structure of dominance of Lepidoptera and  morphological structure as basic determination of taxonomy chategory of LCI plant Lhoknga Kabupaten Aceh Besar. The study was conducted from April to June 2012. The area of the study was divided into four locations; Gunung Bale Area (location I), Gunung Badak Area (Location II), LCI factory (Location III) and Gunung Oshing (location IV). The methods were survey and capture. The structure of the dominance was analysed by dominance formula and the species was analysed descriptivelly. The findings showed that there were 13 species and 1 species with dominance index (ID)  were  0.0-0.25 and 0.26-0.50 respectivelly, and none of them with ID ˃ 0.50. The species can be potentially used as the learning media of the course were 13 species, including the morphology and anatomy of each species. The parts of the body of Lepidoptera comprising of podos, chephal, torax, abdomen, and ptera are the basic determination of the taxonomy. In brief, it was found that Lepidoptera with categories were sub-dominant and not dominant. Determination of the taxonomy relied on the various structure of morphology of each members of Lepidoptera according to examinated level of taxonomy.